Compartment and signal-specific codependence in the transcriptional control of Salmonella periplasmic copper homeostasis - Pezza, Alejandro (2016)
Copper homeostasis is essential for bacterial pathogen fitness and infection, and has been the focus of a number of recent studies. In Salmonella, envelope protection against copper overload and macrophage survival depends on CueP, a major copper-binding protein in the periplasm. This protein is also required to deliver the metal ion to the Cu/Zn superoxide dismutase SodCII. The Salmonella-specific CueP-coding gene was originally identified as part of the Cue regulon under the transcriptional control of the cytoplasmic copper sensor CueR, but its expression differs from the rest of CueR-regulated genes. Here we show that cueP expression is controlled by the concerted action of CueR, which detects the presence of copper in the cytoplasm, and by CpxR/CpxA, which monitors envelope stress. Copper-activated CueR is necessary for the appropriate spatial arrangement of the -10 and -35 elements of the cueP promoter, and CpxR is essential to recruit the RNA polymerase. The integration of two ancestral sensory systems-CueR, which provides signal specificity, and CpxR/CpxA, which detects stress in the bacterial envelope-restricts the expression of this periplasmic copper resistance protein solely to cells encountering surplus copper that disturbs envelope homeostasis, emulating the role of the CusR/CusS regulatory system present in other enteric bacteria.